Ukraine defense sufficiency as a factor of restraining military aggression against Ukraine - Zamana V. М. (Honor and Law, 2019)
Dug and place of Ukraine Armed forces in provision defense sufficiency of the country, influences upon it internal and external factor, problem-solving questions in provision defense ability Ukraine and fighting efficiency Armed forces, as well as possible ways of its decisions are analyzed.